Phonon arithmetic in a trapped ion system - Mark Um (Nature Portfolio, 2016)
Single-quantum level operations are important tools for engineering desired quantum states, but they are inherently probabilistic operations with low experimental success rate. Here, the authors demonstrate near deterministic addition and subtraction of a single phonon of motion in a trapped Yb ion.